Acolhimento em serviços de saúde brasileiros de ocorrência de parto da rede cegonha na perspectiva das usuárias - NUNES, Ana Lúcia (2021)
Reception can be understood as a technology that enables favorable conditions for care in a timely manner in the health system, regardless of any social and reproductive condition. Thus, the objective of this dissertation is to evaluate the sociodemographic and reproductive factors associated with the reception in Brazilian health services of occurrence of birth of Rede Cegonha from the perspective of users. This is a cross-sectional study with data from the Survey on the Evaluation of Good Practices in Childbirth and Maternity Care in the ambit of the Rede Cegonha, carried out in 2017. Health services were selected where there were parts during the study period, totaling 606 services and a sample of 10.540 puerperal women. In the proposed theoretical model, the outcome variable was embracement understood as the relationships between those involved in the care provided in health services. The explanatory variables were: age, education, skin color, marital status, type of delivery, parity, and access/pilgrimage to services. It was to use equation modeling, which will evaluate the effects of the explanatory variables. The highest percentage of municipal managed health services (62.2%), general hospital (81.9%), of usual risk (79.3%), with a size of fewer than 50 beds (85.0%). They had a direct positive effect on the reception in health services where births occurred, age (CP = 0.094; p <0.001) and education (CP = 0.096; p <0.001) and a negative direct effect on skin color (CP = -0.081; p <0.001) and the type of delivery (CP = -0.059; p <0.002). It is concluded that puerperal women over the age of twenty, with higher education and vaginal delivery, evaluated that they were better received in Brazilian health services. Worse reception by health services and professionals persists for puerperal women of brown or black color and of lower age and less education.